Brewing Time Affects the Total Phenol Content and Antioxidant Activity of Combined Herbal Teas - Kusnul, Zauhani; Afridah, Wiwik; Basuki, Duwi (International Conference on Biomedical and Sports Medicine, 2025)
Abstract. Various natural products have been studied to have positive benefits in increasing endurance/immunity, including meniran leaves, moringa leaves, pegagan leaves and green tea leaves. We combine various natural ingredients with these properties in the form of herbal tea formulations. Next, we conduct an analysis process to measure the total phenol content and antioxidant activity of this herbal tea formula with variations in brewing duration. The purpose of this study was to prove the effect of brewing duration on the total phenol content and antioxidant activity of herbal tea formulas. The study was conducted in the chemistry laboratory of the State Polytechnic of Malang. The results of this study indicate that the brewing duration has a positive effect on the total phenol content and antioxidant activity of herbal tea. Furthermore, research needs to be conducted to determine the maximum duration that is still effective for the herbal tea brewing process as well as the effect of the brewing water temperature. The results of this study will be important information for the public to get optimal benefits from herbal tea with the correct processing and serving techniques..